Susceptibilidad y mecanismos de resistencia a insecticidas en Anopheles albimanus del sur de la Península de Yucatán, México Susceptibility and inseticide resistance mechanisms in Anopheles albimanus from the southern Yucatan Peninsula, Mexico - Felipe A. Dzul; R. Patricia Penilla; Américo D. Rodríguez (Instituto Nacional de Salud Pública, 2007)
OBJETIVOS: Diagnosticar la resistencia a insecticidas y sus mecanismos en Anopheles albimanus del sur de la Península de Yucatán (PY), México. MATERIAL Y MÉTODOS: La F1 de An. albimanus colectados durante noviembre-diciembre de 2005 en seis localidades de los municipios Othón P. Blanco en Quintana Roo y Calakmul en Campeche, fue sometida a pruebas de susceptibilidad con deltametrina, DDT, pirimifos metil y bendiocarb, y a pruebas bioquímicas para calcular los niveles de las enzimas involucradas en la resistencia. RESULTADOS: An. albimanus fue resistente al DDT y a deltametrina en las seis localidades con niveles elevados de glutatión S-transferasas (GSTs), monooxigenasas y esterasas, y a pirimifos metil en La Unión con una alta frecuencia de la acetilcolinesterasa (AChE) alterada. CONCLUSIÓN: Las poblaciones de An. albimanus colectadas al sur de la PY son resistentes al DDT y deltametrina, y en La Unión además al pirimifos metil, con mecanismos basados en la AChE alterada para el pirimifos metil, GST para DDT, y monooxigenasas y esterasas para piretroides. Los resultados del presente estudio tienen importantes consecuencias prácticas para el control químico de An. albimanus en el sur de la PY. OBJECTIVE: To diagnose susceptibility levels and insecticide resistance mechanisms in Anopheles albimanus from the southern Yucatan Peninsula (YP), Mexico. MATERIAL AND METHODS: F1 generation of An. albimanus females, collected from November to December 2005 in six villages in the Othon P. Blanco municipality in Quintana Roo and the Calakmul municipality in Campeche, were exposed to deltamethrin, DDT, pirimiphos-methyl and bendiocarb in susceptibility tests, as well as to biochemical assays in order to calculate the enzyme levels related to insecticide resistance. RESULTS: High levels of DDT and deltamethrin resistance were found in An. albimanus collected from the six villages, and a high resistance to pirimiphos-methyl was found in those from La Union, Quintana Roo. Biochemical assays showed high levels of glutathione S-transferase (GST), cytochrome P450 and esterases (with pNPA substrate) in all villages. The frequency of An. albimanus with altered acetylcholinesterase (AChE) was high in La Union (33%). CONCLUSIONS: The An. albimanus populations collected in the south of the YP are resistant to DDT and deltamethrin, whereas resistance to pirimiphos-methyl was significant only in those collected from La Union. The mechanisms explaining this resistance are based on high concentrations of GST, cytochrome P450 and esterasas, the former being responsible for DDT metabolism and the others for pyrethroid metabolism. The altered AChE was the mechanism correlated to pirimiphos-methyl resistance in La Union. The results of the present study have important practical consequences for the chemical control of An. albimanus in the south of the YP.